GAMBARAN POLA MAKAN PADA ANAK REMAJA PENYANDANG AUTIS DI KOTA JAKARTA - Ayunita Sugiarti (2023)
Autism is a developmental disorder that causes obstacles to socialization, communication and behavior. Data from UNESCO and the CDC show a rapid increase in the number of people with autism in recent years. Previous research has shown that diet can influence behavior and symptoms in people with autism. This study aims to provide an overview of the influence of the diet of autistic teenagers in the city of Jakarta using a qualitative approach, because information regarding this topic is still limited. This study uses a qualitative descriptive method, the sample is 12 mothers/guardians who have autistic teenagers. Data were collected for types of food ingredients and frequency of consumption through food frequency questionnaires and in-depth interviews. The results showed that the most frequently consumed food ingredients were carbohydrates (rice), animal protein (chicken eggs), seafood (tilapia fish/goldfish), nuts (tempeh), vegetables (carrots), fruit (bananas). The eating pattern of teenagers with autism is largely influenced by family influences, especially the mother as a regulator of food in the family. A total of eight respondents (out of 12 respondents) implemented a gluten-casein-free diet and six respondents with an additive-free diet. All respondents have a regular eating pattern. Meanwhile, 58% respondents with picky eaters.